Advances in Bridge Engineering - Qin, Shunquan; Li, Yongle; Cai, Steve C.S.; Hao, Hong.; Sun, Liming; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer.)
Advances in Bridge Engineering (ABE) is an open access journal sponsored by Southwest Jiaotong University in China. It aims to form an international platform for the academic and technical communication on the timely progress in bridge engineering. It is also a significant place to share the latest achievements in bridge engineering between China and the world. Topics include but not are limited to: Innovation in the structural styles of bridges Innovation and application of new materials Loads determination and effects evaluation Static and dynamic behavior for complex bridges Resistance of wind, seismic or other disasters Dynamic effects and running safety of the traffic on bridges Health monitoring and damage identification State assessment, reinforcement, and maintenance Artificial intelligence and big data Construction technology innovation Bridges for new types of transportation Interdisciplinary innovation and application.
Keywords: Engineering; Civil engineering; Civil Engineering; Engineering, general